Da'wah Methodology: Counseling Techniques as a Tool of Da'wah - Mohd Rizuan Ishak (Universiti Sains Islam Malaysia, 2022)
The study of da'wah and its methodologies has been conducted a lot, the reason is to study the most efficient methods in performing da'wah. This study focusing on counseling as one of the methods. It will be viewed from technical aspects in counseling, so the appropriate technique that suits da'wah interest can be applied. The techniques used in counseling has it own privilege. There the techniques should be explored. In order to collect information, I've conducted library research and interviews with the practitioners. The result show the similarly methods between da'wah and counseling. This statement is also been supported by the experts in both fields particularly from YADIM and PERKAMA. Thus, this study has found a new method to perform da'wah by using counseling techniques that have been adopted with da'wah.